Chemical and sensory properties of analogue rice produced from maize grits and high quality cassava flour blends - Karim, O.R.; Olapade, G.; Awoyale, W.; Maziya-Dixon, Busie; Oyeyinka, S.; Olawuyi, I. (2017)
In order to reduce the large quantity of rice imported into Nigeria on a yearly basis, there is the need to get an alternative food that resembles rice to meet domestic requirement and food diversification. This work was therefore designed to determine the chemical, functional and sensory properties of analogue rice (ARC) produced from five blends of maize grits and high quality cassava flour (HQCF) using standard methods. The sensory qualities and consumer acceptability of the ARC were compared with imported rice. Significant differences (p<0.05) existed between the chemical and functional properties of the ARC and reference samples, though most of the values are within the acceptable levels for rice grain and cassava products. The moisture (3.68% to 5.34%); ash (0.50 to 0.68%); fibre (1.57 to 2.47%) and oil absorption capacity (1.75to 2.00%) values were reducing, while the carbohydrate; (85.18 to 86.12 %); cyanogenic potentials (8.22 to 9.35mgHCN/kg); water (2.50 to 3.10%) and swelling absorption (9.85 to 12.04%) capacities were increasing as the level of HQCF increases. The sensory and consumer acceptability results showed that the ARC from 75% maize grits and 25% HQCF blend was the most preferred.